ALBERT CAMUS, THE ABSURD AND MARTYRDOM BY ARIEF S. ARMAN:: A REJOINDER - Malick Elias (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2021)
Thank you for another insightful edition of the Al-Shajarah, ISTAC Journal of Islamic Thought and Civilisation, Volume 26, Number 1, 2021. Moreover, an extended appreciation for the opportunity to post this rejoinder to the above-named article. At a glance, ‘martyrdom’ captures the attention and conjures questions, especially when positioned with Camus’ absurdism often read as the ‘meaninglessness.’ But ‘suicide’ defined as killing oneself, and a suicide attack as killing oneself and others in the process is not martyrdom. Etymologically, in the old English, a ‘martyr’ is a ‘witness’ originating from the Greek ‘mártur’ and this meaning is consistent with the Arabic term shahīd, literally a witness. Arman is not conflating the two, but one has to read some distance into the article to determine that.